2023
DOI: 10.3390/buildings13020452
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Environmental Performance Enhancement Strategies and Building Data Capturing Techniques in the Nigerian Context

Abstract: The need to improve the performance of Nigeria’s office buildings is due to, energy challenges, increasing population, changing user needs, and climate change. With the expansion of several Nigerian cities, existing buildings constitute a significant portion of the building stock, and improving their environmental performance could be more cost-effective than reconstruction. The use of simulation packages to assess alternative retrofitting enhancement scenarios is a straightforward approach. However, in Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…According to (Mustaffa, Isa, Ekundayo and Joseph 2022), a societies awareness levels of issues surrounding global warming and climate change infers that the society is on the path of transitioning to minimizing the environmental impacts of construction projects on the built environment. Energy challenges which has arisen due to huge surges in urban population figures has further exacerbated changes in user needs which are having devastating consequences on the environmental sustainability of the environment thereby further contributing to the effects of buildings on climate change (Omoragbon, Al-Maiyah and Coates 2023). It was further observed that energy consumption in buildings depends on two major conditions which affect building energy use according to (Akram, Hasannuzaman, Cuce and Cuce 2023).These authors further believe that these multiple conditions are categorized further namely factors directly linked to the environment and factors relating to design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Mustaffa, Isa, Ekundayo and Joseph 2022), a societies awareness levels of issues surrounding global warming and climate change infers that the society is on the path of transitioning to minimizing the environmental impacts of construction projects on the built environment. Energy challenges which has arisen due to huge surges in urban population figures has further exacerbated changes in user needs which are having devastating consequences on the environmental sustainability of the environment thereby further contributing to the effects of buildings on climate change (Omoragbon, Al-Maiyah and Coates 2023). It was further observed that energy consumption in buildings depends on two major conditions which affect building energy use according to (Akram, Hasannuzaman, Cuce and Cuce 2023).These authors further believe that these multiple conditions are categorized further namely factors directly linked to the environment and factors relating to design parameters.…”
Section: Introductionmentioning
confidence: 99%